2018
DOI: 10.1177/2053951718784083
|View full text |Cite
|
Sign up to set email alerts
|

Datafication and data fiction: Narrating data and narrating with data

Abstract: Data do not speak for themselves. Data must be narrated-put to work in particular contexts, sunk into narratives that give them shape and meaning, and mobilized as part of broader processes of interpretation and meaning-making. We examine these processes through the lens of ethnographic practice and, in particular, ethnography's attention to narrative processes. We draw on a particular case in which digital data must be animated and narrated by different groups in order to examine broader questions of how we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 35 publications
0
94
0
6
Order By: Relevance
“…HCI and CSCW researchers have studied how data scientists work with their data (e.g., [11,46,48,50,53,54]). Passi and Jackson examined how data science workers deal with rules with doing data science and concluded that most scholars use rules as a basis and framework ("rules-based") but not as a set of required ways-of-working (i.e., not "rules-bound") [53].…”
Section: Human Intervention In Data Sciencementioning
confidence: 99%
“…HCI and CSCW researchers have studied how data scientists work with their data (e.g., [11,46,48,50,53,54]). Passi and Jackson examined how data science workers deal with rules with doing data science and concluded that most scholars use rules as a basis and framework ("rules-based") but not as a set of required ways-of-working (i.e., not "rules-bound") [53].…”
Section: Human Intervention In Data Sciencementioning
confidence: 99%
“…Kitchin (2013) also makes a similar point, noting the underpinning assumptions of exhaustible data collection (where n = all) and maximal data resolution (greatest detail possible) that drive many big data ventures. Assumptions also dominate the field of data science (the growing disciplinary and professional body who work with these systems), with Forsythe (1993) describing how the work of doing AI and the epistemological assumptions behind AI are steeped in tacit assumptions that shape products and underlying knowledge of the system (Dourish, 2016;Dourish & Gómez Cruz, 2018;Frické, 2015;Leonelli, Rappert, & Davies, 2017;Lowrie, 2017). In other words, there are several social assumptions that underlie data abstraction techniques that are disguised or "black-boxed" by their function.…”
Section: Data Abstractionmentioning
confidence: 99%
“…The second class of systems and activities aligns with practices in healthcare, where citizens' (or patient) records are used in the instrumental role of tending to the individual and informing the activities of the care professionals who orbit that individual while they recover [5,27,49,50,54]. Similar activities take place in public services, where social workers enter and track data about individuals to support their progress toward stability.…”
Section: Differences In Classes Of Systemsmentioning
confidence: 99%